Disparities in Uptake of 13-valent Pneumococcal Conjugate Vaccine among Older Adults Following Routine Recommendation in the United States. (4th October 2017) - McLaughlin, John; Khan, Farid; Curry, Aaron; Snow, Vincenza; Isturiz, Raúl; Swerdlow, David
Abstract: Background: In the fall of 2014, the Advisory Committee on Immunization Practices (ACIP) recommended 13-valent pneumococcal conjugate vaccine (PCV13) for all US adults age ≥65 years. Coverage rates are currently unknown. This study estimated overall PCV13 coverage rates in older adults and determined if disparities in uptake existed for some sociodemographic groups. Methods: A monthly series (August 1, 2014 – Feb 28, 2017) of cross-sectional analyses of administrative diagnosis and prescription claims data collected by QuintilesIMS and linked to sociodemographic data collected by Experian were used to estimate overall and subpopulation-level uptake of PCV13 among US adults age ≥65. Uptake estimates were adjusted to PCV13 manufacturer sales data to account for missingness patterns in QuintilesIMS claims data. Univariate and multivariable analyses of PCV13 uptake were performed across sociodemographic factors (e.g., race/ethnicity, household income, neighborhood urbanicity, education status). Results: Among adults age ≥65, 50% received PCV13 by the end of February 2017. Disparities in PCV13 uptake were apparent. Black adults (39%) and Hispanics (32%) ( vs. 53% for whites), the poor (36% vs. 64% for lowest vs. highest income deciles), adults with low educational status (37% vs. 58% for those without high school education vs. college educated), and those living in rural (33%) or urban/inner city (41%) areas ( vs. 52% in suburban areas) had significantly lower PCV13 uptake (all P < .001) (Figure). These differences persisted in multivariable analyses. Conclusion: PCV13 uptake among adults age ≥65 occurred rapidly after ACIP recommendation in late 2014. Yet, poor and minority communities, rural and urban/inner city areas, and communities with low educational attainment may need more time to adequately implement adult vaccine guidelines following ACIP recommendation. In 2018, current adult pneumococcal recommendations will be revisited by ACIP. Changes to existing recommendations for older adults, however, could cement these disparities in adult PCV13 uptake in the very communities at increased risk for pneumococcal disease. These vulnerable communities may instead benefit from targeted and tailored interventions to increase pneumococcal vaccination. Disclosures: J. McLaughlin, Pfizer Inc: Employee and Shareholder, Salary; F. Khan, Pfizer Inc: Employee and Shareholder, Salary; A. Curry, Pfizer Inc: Employee and Shareholder, Salary; V. Snow, Pfizer Inc: Employee and Shareholder, Salary; R. Isturiz, Pfizer Inc: Employee and Shareholder, Salary; D. Swerdlow, Pfizer Inc: Employee and Shareholder, Salary